EFEKTIVITAS KOMUNIKASI DALAM PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 DI KOTA MAKASSAR - Amalia Zul Hilmi; Soraya Firdausy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2021)
Online learning is the main means of learning when the Covid-19 pandemic is still spreading. Makassar City is no exception, every university also requires students to carry out online learning by utilizing existing digital media applications. This study aims to analyze the effectiveness of communication in online learning during the Covid-19 pandemic in Makassar City. By distributing questionnaires to 100 student respondents in Makassar City, it was found that 51% of students use mobile devices and as many as 65% of respondents use the Zoom application as an online learning medium. Furthermore, it is known that the communication interaction between lecturers and students is quite effective so that students are able to understand the material presented during online learning.